Facial talon in mandibular incisor: An unusual occurrence - Prasanna Kumar Rao; Rohan Mascarenhas; Shishir Ram Shetty (Wolters Kluwer Medknow Publications, 2011)
Talon cusp, also known as an eagle's talon, is a dental anomaly that occurs on the lingual aspect of teeth commonly, but occurrence on the facial aspect has rarely been reported. It is an extra cusp on an anterior tooth, which arises as a result of evagination on the surface of a crown before calcification has occurred. The incidence of talon cusp on lingual side is less than 6% and is even lesser on the facial aspect. Commonly involved teeth are maxillary incisors, usually unilateral but in some instances bilateral. The classical radiographical feature of talon cusp is double teeth appearance. The anomaly has been reported to be unusual in the mandibular dentition and extremely rare on the facial aspect. We report one such extremely rare case of facial talon cusp in mandibular central incisor.